The impact of skin diseases on quality of life: A multicenter study (2017)
ABSTRACT: Introduction: To date, no formal study has been published regarding how Colombian patients with skin disorders could be affected according to their perception of disease. Objective: To determine the impact in quality of life of skin diseases in a Colombian population. Methods: This multicenter study included patients with skin disease from almost the whole country. Individuals >18 years old; of any gender; with any skin disease and who signed informed consent, were included. We applied the Colombian validated version of the Skindex-29 instrument. Results: A total of 1896 questionnaires had sufficient information for the analyses. No significant differences in sociodemographic characteristics of patients who returned the questionnaire incomplete vs. complete, were found. Participants mean age was 41.5 years. There were no statistical differences in men vs. women regarding the global (p=0.37), symptoms (p=0.71) and emotions (p=0.32) domains, whereas statistical differences were found in the function domain (p=0.04; Mann-Whitney U test). Psoriasis, contact dermatitis, atopic dermatitis, urticaria, hair disorders, Hansen's disease, scars, hyperhidrosis and genital human papillomavirus disease scored the highest. Limitations: Skindex-29 score variability as a result of differences in the location of the skin lesions, their inflammatory or non-inflammatory nature, and the start of therapy. Conclusions: Even the most localized or asymptomatic skin lesion in our population leads to a disruption at some level of patient's wellness. This study adds well supported scientific data of the burden of skin diseases worldwide.